HISTORIOGRAFI KEPEMIMPINAN ISLAM DALAM PERSPEKTIF FRED M. DONNER DAN RELEVANSINYA BAGI PENDIDIKAN ISLAM - Asroni, Ahmad; Ma’rifah, Indriyani (STKIP Pesisir Selatan, 2025)
This article examines the historiography of Islamic leadership from the perspective of Fred M. Donner and its relevance to Islamic education. Through his works, Donner offers a new perspective that significantly contributes to Islamic studies in general, as well as to the study of Islamic civilization and education, particularly in understanding the historiography of Islamic leadership. This study employs a library research approach with a historical perspective. The data collection method used is documentation, which involves reviewing and analyzing various primary and secondary sources related to Fred M. Donner’s thoughts on the historiography of Islamic leadership and its relevance to Islamic education. The findings reveal that Donner employs four main approaches in studying early Islamic history: the descriptive approach, source-critical approach, tradition criticism, and skeptical approach. Furthermore, according to Donner, there are five historiographical themes concerning leadership in Islam: the fitna (civil strife), sirah al-khulafa (biographies of the caliphs), Pre-Islamic Arabia, Pre-Islamic Iran, and riddah (apostasy wars). Donner’s historiographical approach exhibits several key characteristics that make it relevant to Islamic education: the importance of critical engagement with Islamic historical sources, the necessity of an interdisciplinary approach in Islamic studies, and the need to reconstruct the understanding of Islamic leadership.